2013
DOI: 10.1186/1471-2458-13-449
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in older people: a systematic review

Abstract: BackgroundPhysical activity (PA) in older people is critically important in the prevention of disease, maintenance of independence and improvement of quality of life. Little is known about the physical activity of the older adults or their compliance with current physical activity guidelines.MethodsA systematic literature search of the published literature was conducted. Included were published reports of original research that independently reported: the PA level of non-institutional older adults (aged 60 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
541
11
33

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 784 publications
(657 citation statements)
references
References 61 publications
36
541
11
33
Order By: Relevance
“…Analysis of world literature indicates that comparing the percentages of people engaging in health-enhancing physical activity is difficult due to the multiplicity of methods of assessment and recommendations (recommendations), according to which the results are interpreted. Sun and Norman [16], by making a meta-analysis during 2001-2011 concerning the implementation of the recommendations of physical activity by persons over 60 years of age, that the criteria for health-promoting interests ranged in extreme cases from 2.4 -83%.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of world literature indicates that comparing the percentages of people engaging in health-enhancing physical activity is difficult due to the multiplicity of methods of assessment and recommendations (recommendations), according to which the results are interpreted. Sun and Norman [16], by making a meta-analysis during 2001-2011 concerning the implementation of the recommendations of physical activity by persons over 60 years of age, that the criteria for health-promoting interests ranged in extreme cases from 2.4 -83%.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific literature has pointed to the benefits that physical activity practice provides to the elderly, being important in disease prevention, maintenance of independence and improving quality of life (11)(12) . Frailty is one of the most important reasons to prescribe physical exercise, as this is considered a protective factor against various components of the condition being studied (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity, even in late life, is known to change, with a number of older people remaining active or increasing their levels of activity over time (Martinson et al 2003;Xue et al 2012). A systematic review of the global trends in physical activity in the older population found an increasing participation in leisure-time physical activity among developed countries (Sun et al 2013). Examining whether a maintained or increased physical activity over time is associated with a reduced risk of cognitive decline would have important clinical and public health implications for promoting an active lifestyle for older people.…”
Section: Introductionmentioning
confidence: 99%